2019
DOI: 10.3390/en12102018
|View full text |Cite
|
Sign up to set email alerts
|

Energy Consumption and Trade Openness Nexus in Egypt: Asymmetry Analysis

Abstract: Trade openness may support the economic growth of any country but its environmental effects due to increasing energy consumption cannot be ignored. This research hypothesizes the asymmetrical effects of both economic growth and trade openness on the energy consumption of Egypt from 1971–2014. Our estimates suggest that both economic growth and trade openness have asymmetrical effects on the energy consumption in both long and short runs because magnitude of the effects are found unequal. Both increasing and de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 29 publications
1
14
0
Order By: Relevance
“…The results also indicate that the macroeconomic segment and trade segments are directly and significantly related to each other. Another study that supports a similar idea in the context of Egypt was conducted by Alkhateeb and Mahmood (2019) who mentioned that while trade can lead to economic growth in a country, it does intensify the consumption level of energy, which in turn can increase the CO2 emissions that a country produces. An increase in the income or improvement in the economic growth levels of a country can increase energy consumption as well which can have an environmental degradation impact on the country in general.…”
Section: Literature Reviewmentioning
confidence: 66%
“…The results also indicate that the macroeconomic segment and trade segments are directly and significantly related to each other. Another study that supports a similar idea in the context of Egypt was conducted by Alkhateeb and Mahmood (2019) who mentioned that while trade can lead to economic growth in a country, it does intensify the consumption level of energy, which in turn can increase the CO2 emissions that a country produces. An increase in the income or improvement in the economic growth levels of a country can increase energy consumption as well which can have an environmental degradation impact on the country in general.…”
Section: Literature Reviewmentioning
confidence: 66%
“…Other than an inverted U-shaped curve, both inverted N and M-shaped relationship can vary in different periods. Alkhateeb and Mahmood (2019) found the positive effect of trade openness on energy consumption. Moutinho et al (2017) tested the existence of EKC in Portuguese and Spanish economies and provided evidence of an inverted N-shaped EKC.…”
Section: Theoretical Frameworkmentioning
confidence: 98%
“…Siddiqui et al [34] found the asymmetrical effects of oil price on the stock markets in some Asian countries. Alkhateeb and Mahmood [35] found the asymmetrical effects of trade openness on energy consumption in Egypt. Hence, the asymmetrical effects of trade openness can also be expected on CO 2 emissions.…”
Section: Literature Reviewmentioning
confidence: 99%